YouTube in Research Course Learning: Undergraduates’ Perspectives from a Quantitative Study - Mohd Noor, Nurul Hidayana; Nordin, Nur Batrisyia; Abdullah Hadi, Hasnatulsyakhira; Mohamad Fadzil, Nurin Farzana; El Ashfahany, Afief (Journal of ICT in Education, 2025)
YouTube is a video-sharing site that allows users to watch and share video clips. Past studies have found that online videos, such as YouTube, have been widely used in learning in the classroom and are also commonly used in courses in addition to podcasts, wikis, and blogs. YouTube is also used to encourage self-learning and repetition, and is an educational instrument that improves learning innovatively and creatively. However, many educators would prefer to use technology in their teaching strategy. Educators can no longer remain in a comfort zone with traditional teaching methods, but instead, equip themselves with the latest knowledge and skills. This research explores the influence of system, interaction, and content factors on students' satisfaction with YouTube and their subject performance. Using a systematic sampling, the data were collected using a survey approach from the final-year undergraduate students at Universiti Teknologi MARA (UiTM), Negeri Sembilan. The structural equation modeling technique examined the research model based on the final data of 212 undergraduate students. The results indicate that system, interaction, and content factors statistically affect students' satisfaction. On the other hand, system and content factors significantly influence subject performance. The results of this study show that YouTube videos can stimulate creativity, student interest, satisfaction, and motivation. As implications, universities must plan and formulate targeted training and development programs for educators to ensure they remain relevant in fast-changing educational settings.